Psychometric Testing of the Self-care of Hypertension Inventory Version 3.0. Issue 5 (10th September 2021) - Dickson, Victoria Vaughan; Fletcher, Jason; Riegel, Barbara
Abstract : : In this updated Self-care of Hypertension Inventory Version 3.0 (SC-HI v3.0), items were added to better reflect the Theory of Self-care of Chronic Illness and revised based on recent research. The reorganized and expanded SC-HI now reflects the theoretical concepts of self-care maintenance, monitoring, and management. Objective: To evaluate the psychometric properties of the SC-HI v3.0, we conducted exploratory factor analyses. Here, we report on its reliability and construct validity. Methods: A sample of 200 adults with chronic hypertension completed a sociodemographic survey and the SC-HI v3.0. Exploratory factor analyses were conducted on item sets using principal factor method for analyzing the correlation matrix. Reliability was calculated using common factor coefficient of determinacy for multidimensional scales, for which values greater than 0.80 are considered adequate. Results: The sample was 83.4% non-Hispanic White; 56% were women, with a mean age of 62.2 ± 12.5 years. The self-care maintenance scale (mean, 75.9 ± 13.6) had adequate reliability ( ρ = 0.81, 0.80) for a 2-dimensional model of self-care maintenance identified as autonomous and consultative behaviors. The new self-care monitoring scale (mean score, 58.5 ± 21.99) had a single-factor solution with very good reliability ( ρ = 0.94). The self-care management scale (mean score, 64.5 ± 19.5) had a single-factor solution, with moderate to strong factor loadings (0.22–0.68) and acceptable reliability ( ρ = 0.84). Conclusions: Initial testing suggests that the SC-HI v3.0 is a sound measure of the essential elements of self-care for adults with chronic hypertension. With the new self-care monitoring scale, the SC-HI v3.0 is a valid reflection of the theory on which it is based.